KRITERIA KEVALIDAN MEDIA PEMBELAJARAN PAKABI (PAPAN KANTONG BILANGAN) UNTUK PEMBELAJARAN MATEMATIKA MATERI NILAI TEMPAT BILANGAN KELAS II SD - Pita Wulandari; Abdul Aziz Hunaifi; Frans Aditia Wiguna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the lack of students’ understanding of the concept of place value in numbers. One contributing factor is that the teacher does not utilize any instructional media during the learning process, which can hinder students’ comprehension of the material. A fun and engaging learning process in teaching the concept of place value can help enhance students' understanding. One way to create an enjoyable learning experience is by using instructional media, such as PAKABI (Papan Kantong Bilangan). This research uses the Research and Development (R&D) method with the ADDIE model. The aim of this study is to describe the validity of the PAKABI (Papan Kantong Bilangan) instructional media. The research instrument used is a validation questionnaire. Based on the results from expert validators: (1) media expert validation received a score percentage of 82%, which falls into the “very valid” category, and (2) material expert validation received a score percentage of 95%, also categorized as “very valid.” Overall, the average validation score is 88.5%, indicating that the PAKABI media is highly valid and can be used in the learning process